Magnetic fluorescent gold nanocluster molecularly imprinted polymer as well as preparation method and application thereof
Through the preparation of magnetic fluorescent gold nanocluster molecularly imprinted polymers, the problem of complex and costly detection of sulfonamide antibiotics in the prior art is solved, and a rapid and accurate detection effect in complex substrates is achieved.
Patent Information
- Application Number
- CN202411414160.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art has insufficient cost, complex instruments, and long training time for operators in detecting sulfonamide antibiotics, making it difficult to achieve simple, fast and efficient detection in complex substrates.
Magnetic fluorescent gold nanocluster molecular imprint polymer was used to coat Fe3O4 nanoparticles by sol-gel method, and combined with gold nanocluster and molecular imprint technology, magnetic fluorescent gold nanocluster imprint polymer with specific recognition ability was prepared. , used for efficient and accurate detection of sulfadiazine in water environment.
It realizes rapid and accurate detection of sulfadiazine in complex substrates, with excellent fluorescence stability and high efficiency specificity, is easy to operate, is relatively low in cost, and is suitable for practical applications.
Smart Images

Figure CN119431793A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of analytical chemistry, and in particular relates to a magnetic fluorescent gold nanocluster molecular imprinting polymer and a preparation method and application thereof. Background Art
[0002] Sulfadiazine, as a kind of sulfonamide antibiotic, is widely used due to its excellent antibacterial properties. At present, sulfadiazine is widely used to prevent and treat epidemic meningitis, and can also be used to treat respiratory infections and local soft tissue infections caused by bacteria. Sulfadiazine is widely used in aquaculture due to its low price and wide antibacterial range. However, due to its stable structure and difficulty in natural degradation, sulfadiazine has excessive residues in water and soil, thus endangering the ecological environment, and will enter the human body through the ecological cycle, endangering human health.
[0003] At present, the main methods for detecting sulfonamide antibiotics include high performance liquid chromatography, electrochemical detection, immunoassay, etc. However, these technologies generally have shortcomings such as high cost, complex instruments, and long operator training time. Therefore, it is very important to develop a simple, rapid and efficient detection technology in complex matrices. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a magnetic fluorescent gold nanocluster molecular imprinted polymer, and use the prepared magnetic fluorescent gold nanocluster molecular imprinted polymer for efficient and accurate identification and detection of sulfadiazine in an aquatic environment.
[0005] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing a magnetic fluorescent gold nanocluster molecular imprinted polymer, comprising the following steps:
[0006] S1, Fe3O4 nanoparticles were coated with silica using a sol-gel method to obtain Fe3O4 nanoparticles coated with silica shell, which were recorded as Fe3O4@SiO2;
[0007] S2, dispersing Fe3O4@SiO2 in anhydrous ethanol, and then adding 3-aminopropyltriethoxysilane for surface modification to obtain amino-functionalized Fe3O4@SiO2, recorded as Fe3O4@SiO2-NH2;
[0008] S3, using the surface modification method, Fe3O4@SiO2-NH2 was combined with gold nanoclusters to obtain Fe3O4@SiO2@AuNCs;
[0009] S4. Using molecular imprinting technology, sulfadiazine was used as the template molecule and a mixed silane coupling agent was used as the functional monomer to coat the molecular imprinting layer on the surface of Fe3O4@SiO2@AuNCs to prepare magnetic fluorescent gold nanocluster imprinted polymer Fe3O4@SiO2@AuNCs-MIPs.
[0010] As a further improvement of the preparation method of the magnetic fluorescent gold nanocluster molecular imprinted polymer:
[0011] Preferably, the preparation method of Fe3O4@SiO2 in step S1 is as follows: adding Fe3O4 nanoparticles to a 0.1-0.3M HCl aqueous solution in an amount of 0.01-0.03g / ml, ultrasonically dispersing for 20-50 minutes, separating and washing to obtain surface-modified Fe3O4 nanoparticles; mixing anhydrous ethanol, distilled water, ammonia water and tetraethyl orthosilicate in a volume ratio of 32:8:1:1 to obtain a mixed solution; adding 200-220ml of the mixed solution to 400-600mg of the surface-modified Fe3O4 nanoparticles and stirring overnight, separating the product, washing with distilled water, and vacuum drying to constant weight. The obtained black powder is Fe3O4 nanoparticles coated with a silica shell, recorded as Fe3O4@SiO2.
[0012] Preferably, the specific preparation method of Fe3O4@SiO2-NH2 in step S2 is as follows: disperse Fe3O4@SiO2 in anhydrous ethanol with a dispersion concentration of 0.01-0.03 g / ml, then add 3-aminopropyltriethoxysilane in anhydrous ethanol in an amount of 0.05-0.1 g / ml, the mass ratio of Fe3O4@SiO2 to 3-aminopropyltriethoxysilane is 1:(4.5-5), and stir the reaction under a protective atmosphere for 10-15 hours, then separate, wash with ethanol, and dry to obtain amino-functionalized Fe3O4@SiO2, recorded as Fe3O4@SiO2-NH2.
[0013] Preferably, the specific preparation method of Fe3O4@SiO2@AuNCs in step S3 is as follows:
[0014] 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is dissolved in morpholineethanesulfonic acid with a concentration of 0.1 mM and a pH of 7.0, and the dissolved concentration is 0.5-2 mg / ml to obtain a hydrochloride solution; N-hydroxysuccinimide is dissolved in distilled water, and the dissolved concentration is 0.5-2 mg / ml to obtain an N-hydroxysuccinimide solution; 90 mL of ultrapure water and 4 mL of 40-60 mM tetrahydrate of chloroauric acid are mixed and stirred evenly to obtain solution 1; 80-100 mg of L-reduced glutathione GSH is dissolved in 4 mL of ultrapure water to obtain solution 2; Solution 2 is added to Solution 1, heated to 60-80° C. and stirred vigorously, and after the solution turns slightly yellow, 1 mL of 28-32% (w / v) threonine Thr aqueous solution is added, and the mixture is reacted. The product should be dialyzed overnight using a dialysis bag for 20-25 hours to obtain a solution containing carboxyl-functionalized gold nanoclusters AuNCs; the hydrochloride solution and the solution containing carboxyl-functionalized gold nanoclusters AuNCs are mixed, and then N-hydroxysuccinimide solution is added, the volume ratio of the three is 6:10:6, and the mixture is stirred; 50-70 mg of Fe3O4@SiO2-NH2 and 0.05-0.2 mM morpholineethanesulfonic acid with a pH of 5-8 are added to the mixture, and the volume ratio of the added volume of morpholineethanesulfonic acid to the solution containing carboxyl-functionalized gold nanoclusters AuNCs is 5:1, after ultrasonic dispersion, stirring overnight in the dark, separation, and washing with a phosphate buffer solution with a pH of 7.0 and a concentration of 0.01 M to obtain Fe3O4@SiO2@AuNCs.
[0015] Preferably, the preparation method of Fe3O4@SiO2@AuNCs-MIPs in step S4 is as follows: 80-150 mg of Fe3O4@SiO2@AuNCs nanoparticles are added to 30-50 ml of phosphate buffer solution and mixed evenly. The concentration of the phosphate buffer solution is 10 mmol L -1 , pH 7.0, then add 0.15-0.2mmol mixed silane coupling agent, add 10mg sulfadiazine as template molecule, stir evenly, add 60-100μl tetraethyl orthosilicate and 60-100μl ammonia water, the molar ratio of template molecule to mixed silane coupling agent is 1:4, stir continuously for 12-20h at room temperature, after the reaction is completed, separate the solid product by centrifugation, then wash repeatedly with a mixed solvent of methanol and acetic acid in a volume ratio of 9:1, until the supernatant can no longer detect the template molecule sulfadiazine by ultraviolet spectrophotometer, and then vacuum dry, so as to obtain magnetic fluorescent gold nanocluster imprinted polymer, recorded as Fe3O4@SiO2@AuNCs-MIPs.
[0016] Preferably, in step S1, the black powder Fe3O4@SiO2 is dried in a vacuum drying oven at a temperature of 40-60°C, and the separated product is washed successively with distilled water and anhydrous ethanol; and the reaction products are separated in steps S1 and S2 by adsorption separation using a strong magnet.
[0017] Preferably, the mixed silane coupling agent described in step S4 is APTES.
[0018] The second object of the present invention is to provide a magnetic fluorescent gold nanocluster molecular imprinting polymer prepared by any of the preparation methods described above.
[0019] The third object of the present invention is to provide an application of the magnetic fluorescent gold nanocluster molecular imprinting polymer in detecting sulfadiazine.
[0020] As a further improvement of the application of the magnetic fluorescent gold nanocluster molecular imprinting polymer in the detection of sulfadiazine:
[0021] Preferably, the aqueous solution of the magnetic fluorescent gold nanocluster molecular imprinting polymer is mixed with sulfadiazine, and the changes in fluorescence intensity before and after the mixing are compared.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1) The electrons inside the metal nanocluster material can be transferred between energy spectra, thereby generating absorption and emission spectra, and have photoluminescence, excellent fluorescence stability and high luminescence efficiency. This excellent luminescence performance makes it widely used in ion detection, fluorescence detection, biological analysis and other fields. Molecular imprinting technology is a means of synthesizing polymers with specific recognition functions for target analytes by chemical methods. Molecular imprinting polymers have many advantages such as specific recognition, environmental stability, convenient synthesis and relatively low preparation cost. Combining gold nanoclusters with molecular imprinting polymers can form a fluorescent molecular imprinting complex with excellent optical properties and selective recognition capabilities.
[0024] The present invention uses magnetic nanomaterials as cores and is coated with a silicon layer, which can provide a larger surface area and better dispersibility than other bare magnetic materials. This magnetic molecular imprinted material with a shell-core structure completely embeds the magnetic particles and is not easy to leak. The recognition site is on the surface of the polymer microspheres, and the binding efficiency and separation efficiency of the target are higher. At the same time, the material has super paramagnetism and can achieve rapid magnetic separation under the action of an external magnetic field, allowing the material to be recycled.
[0025] 2) In step S2, 3-aminopropyltriethoxysilane is a mixed silane coupling agent, sulfadiazine (SD) is a template molecule, tetraethyl orthosilicate is a crosslinking agent, and ammonia water is an initiator.
[0026] The present invention combines the advantages of high selectivity and specificity of molecular imprinting technology, high specific surface area of mesoporous materials, and superior optical properties of gold nanoclusters (AuNCs), and combines the advantages of gold nanoclusters, molecular imprinting polymers and magnetic materials together to synthesize a fluorescent molecular imprinting polymer material with an ordered mesoporous structure with high efficiency and specificity.
[0027] 3) The present invention performs FT-IR characterization and structural characterization on the synthesized molecular imprinting polymer, explores the effects of quenching time, template solutions with different template molecule concentrations and different pH values, and actual samples on the detection of sulfadiazine by fluorescent imprinting polymer, obtains the most suitable detection conditions and obtains good results. The synthesis process of this method is simple to operate, and the elution process of the template molecule is also efficient. The synthesized material has stable chemical and physical properties and can detect sulfadiazine with high specificity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the preparation process of molecularly imprinted microspheres (MIPs) with mesoporous structure;
[0029] Figure 2 It is the infrared spectra of Fe3O4@SiO2 prepared in Example 1, Fe3O4@SiO2@Au NCs prepared in Example 2, and Fe3O4@SiO2@AuNCs-MIPs prepared in Example 3;
[0030] Figure 3 It is the SEM image of Fe3O4@SiO2 prepared in Example 1 and Fe3O4@SiO2@Au NCs-MIPs prepared in Example 3;
[0031] Figure 4 is the magnetization curve of Fe3O4@SiO2@AuNCs-MIPs prepared in Example 3;
[0032] Figure 5 This is a graph showing the change in fluorescence intensity of Fe3O4@SiO2@AuNCs-MIPs prepared in Example 3 as a function of time;
[0033] Figure 6 This is a graph showing the fluorescence quenching response time of Fe3O4@SiO2@AuNCs-MIPs prepared in Example 3 to sulfadiazine;
[0034] Figure 7 This is the effect of sulfadiazine on the fluorescence quenching of Fe3O4@SiO2@AuNCs-MIPs at different pH values;
[0035] Figure 8This is the effect of different concentrations of template molecules on the fluorescence intensity of Fe3O4@SiO2@AuNCs-MIPs;
[0036] Fig. 9 This is the change diagram of the fluorescence quenching of Fe3O4@SiO2@AuNCs-MIPs and Fe3O4@SiO2@AuNCs-MIPs by four sulfonamide antibiotics; DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] This embodiment provides a method for preparing Fe3O4@SiO2-NH2, which specifically includes the following steps:
[0040] S1. Add 2.0 g of Fe3O4 into 100 mL of 0.1 M HCl aqueous solution, and perform ultrasonic dispersion for 30 minutes to modify the surface of Fe3O4. The separated Fe3O4 powder is washed several times with distilled water and ethanol to obtain surface-modified Fe3O4 nanoparticles.
[0041] S2. Absolute ethanol (160 mL), distilled water (40 mL), ammonia water (5 mL) and tetraethyl orthosilicate (5 mL) were vigorously stirred to obtain a mixed solution; the mixed solution was added to the surface-modified Fe3O4 (500 mg) nanoparticles and stirred overnight, the product was separated by strong magnet adsorption, washed with distilled water for multiple times, and vacuum dried at 50°C to constant weight. The obtained black powder was Fe3O4 nanoparticles coated with a silica shell, recorded as Fe3O4@SiO2;
[0042] S3. Take 1g of Fe3O4@SiO2 and disperse it in anhydrous ethanol (50mL) with a dispersion concentration of 0.02g / ml. Then add 3-aminopropyltriethoxysilane (5mL, 4.82g). The amount of 3-aminopropyltriethoxysilane added in anhydrous ethanol is 0.096g / ml. The mass ratio of Fe3O4@SiO2 to 3-aminopropyltriethoxysilane is 1:4.82. Stir for 12 hours under a nitrogen atmosphere until the reaction is completed. Use a strong magnet to separate the synthetic product, wash it repeatedly with ethanol, and place it in a vacuum oven to dry to constant weight to obtain Fe3O4@SiO2-NH2.
[0043] Example 2
[0044] This embodiment provides a Fe3O4@SiO2@AuNC s The preparation method specifically comprises the following steps:
[0045] S1. Dissolve 20 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) in 20 mL of 0.1 mM morpholineethanesulfonic acid (pH=7.0) to a concentration of 1 mg / ml to obtain a hydrochloride solution;
[0046] Dissolve 10 mg of N-hydroxysuccinimide in 10 mL of distilled water to a concentration of 1 mg / ml to obtain an N-hydroxysuccinimide solution;
[0047] 90 mL of ultrapure water and 4 mL of 50 mM tetrahydrate chloroauric acid were mixed and stirred evenly to prepare solution 1; 92 mg of L-reduced glutathione GSH was dissolved in 4 mL of ultrapure water to prepare solution 2; solution 2 was added to solution 1, heated to 70°C and stirred vigorously, and after the solution turned slightly yellow, 1 mL of threonine Thr aqueous solution (concentration of 30%, w / v) was added, and the reaction was allowed to proceed overnight. The product was dialyzed using a dialysis bag for 24 hours to prepare a solution containing carboxyl-functionalized gold nanoclusters AuNCs;
[0048] S2, taking 6 mL of the hydrochloride solution and mixing it with 10 mL of the solution containing carboxyl functionalized gold nanoclusters AuNCs, stirring for 10 minutes, and then adding 6 mL of the N-hydroxysuccinimide solution, stirring for 10 minutes to obtain a mixture;
[0049] S3. Add 60 mg of Fe3O4@SiO2-NH2 prepared in Example 1 and 50 ml of 0.1 mM morpholineethanesulfonic acid (pH = 6) to the mixture, stir overnight in the dark after ultrasonic dispersion, separate, and wash three times with 0.01 M phosphate buffer solution (pH 7.0) to remove unreacted Thr-AuNCs to obtain Fe3O4@SiO2@AuNCs.
[0050] Example 3
[0051] This embodiment provides a method for preparing Fe3O4@SiO2@AuNCs-MIPs, which specifically includes the following steps:
[0052] S1. Take 100 mg of Fe3O4@SiO2@AuNCs nanoparticles prepared in Example 2 and add them to 40 ml of phosphate buffer solution (10 mmol L -1 , pH = 7.0) and mixed evenly;
[0053] S2, add 0.16mmol mixed silane coupling agent (APTES) and 10mg (0.04mmol) sulfadiazine as template molecules, stir for 30min, add 80μL of tetraethyl orthosilicate and 100μL of ammonia water, continue stirring at room temperature for 16h, and after the reaction is completed, centrifuge the solution to separate the solid product;
[0054] S3. The separated solid product was repeatedly washed with a mixed solvent of methanol and acetic acid (v / v=9:1) until the supernatant could no longer detect the template molecule sulfadiazine by ultraviolet spectrophotometer, and then vacuum dried to obtain a magnetic fluorescent gold nanocluster imprinted polymer, which was recorded as Fe3O4@SiO2@AuNCs-MIPs.
[0055] Comparative Example
[0056] This comparative example provides a method for preparing Fe3O4@SiO2@AuNCs-NIPs, which specifically comprises the following steps:
[0057] S1. Take 100 mg of Fe3O4@SiO2@AuNCs nanoparticles prepared in Example 2 and add them to 40 ml of phosphate buffer solution (10 mmol L -1 , pH = 7.0) and mixed evenly;
[0058] S2, add 0.16mmol mixed silane coupling agent (APTES), stir for 30min, then add 80μL of tetraethyl orthosilicate and 100μL of ammonia water, continue stirring at room temperature for 16h, after the reaction is completed, centrifuge the solution to separate the solid product;
[0059] S3. The separated solid product was repeatedly washed with a mixed solvent of methanol and acetic acid (v / v=9:1) until the supernatant could no longer detect the template molecule sulfadiazine by ultraviolet spectrophotometer and then vacuum dried, that is, a magnetic fluorescent gold nanocluster imprinted polymer was obtained without adding the template molecule sulfadiazine, which was recorded as Fe3O4@SiO2@AuNCs-NIPs.
[0060] 1. Preparation process
[0061] Figure 1 The process flow chart of preparing Fe3O4@SiO2@AuNCs-MIPs polymer in the present invention is as follows: Figure 1As shown, the present invention first coats the surface of Fe3O4 nanoparticles with a silica shell and performs surface modification on the shell to obtain Fe3O4 nanoparticles coated with a silica shell, namely, Fe3O4@SiO2; then, Fe3O4@SiO2 is combined with gold nanoclusters (AuNCs), and the molecular imprinting layer is coated on the surface of Fe3O4@SiO2@AuNCs using molecular imprinting technology, using sulfadiazine (SD) as a template molecule and a mixed silane coupling agent (APTES) as a functional monomer, to prepare a magnetic fluorescent gold nanocluster imprinted polymer Fe3O4@SiO2@AuNCs-MIPs.
[0062] 2. Fourier transform infrared spectroscopy (FT-IR) characterization of molecularly imprinted microspheres
[0063] like Figure 2 The Fourier transform infrared spectroscopy (FT-IR) characterization diagrams of the three materials are Fe3O4@SiO2 prepared in Example 1, Fe3O4@SiO2@AuNCs prepared in Example 2, and Fe3O4@SiO2@AuNCs-MIPs prepared in Example 3, respectively. Figure 2 As shown in (a), (b) and (c).
[0064] Figure (a) at 579cm -1 There is an obvious absorption peak at 1562cm -1 and 3421cm -1 The two peaks correspond to the bending vibration and stretching vibration of hydrogen bonds. -1 The characteristic peak is attributed to the vibration of Si-O-Si, 771 cm -1 The characteristic peak at 2947 cm -1 The peak at 1400 cm-1 of CO-NH vibration can be attributed to the carbon-hydrogen stretching vibration of 3-aminopropyltriethoxysilane. Therefore, the surface of Fe3O4@SiO2 is functionalized with amino groups. -1 and 1495cm -1 A peak appears at 574 cm, indicating that the gold nanoclusters are successfully bonded to the silica on the Fe3O4 surface through CO-NH bonds. -1 The peak at may be related to silica; therefore, the IR spectrum proves that the molecularly imprinted microspheres were successfully synthesized.
[0065] 3. Scanning electron microscopy (SEM) characterization
[0066] A small amount of Fe3O4@SiO2 prepared in Example 1 and the magnetic fluorescent gold nanocluster imprinted polymer Fe3O4@SiO2@AuNCs-MIPs prepared in Example 3 were uniformly spread on the gold sheet, and then scanned and the morphology of the samples was observed under an electron microscope. The scanning electron microscope images are as follows: Figure 3 As shown in (a) and (b).
[0067] From Figure (a), it can be seen that the Fe3O4@SiO2 particles are uniform in size and regular spherical, with the particle size concentrated between 130-210nm; from Figure (b), it can be seen that the Fe3O4@SiO2@AuNCs-MIPs particles are irregular spherical with different sizes ranging from 260-550nm, and the particle size is significantly larger than that of Fe3O4@SiO2. As a result, the surface polymer imprinting layer is anchored on the surface of Fe3O4@SiO2.
[0068] 4. Magnetization curve diagram (VSM)
[0069] The magnetic properties of Fe3O4@SiO2@AuNCs-MIPs prepared in Example 3 were determined by a comprehensive physical property measurement system.
[0070] Figure 4 This is the magnetization curve of Fe3O4@SiO2@AuNCs-MIPs at room temperature. It can be seen that the magnetic material has superparamagnetism. Even with the molecular imprinting layer and the silica core coated on the Fe3O4 core, the composite does not show hysteresis. Therefore, the composite has excellent magnetic properties and can be used for magnetic adsorption separation.
[0071] 5. Study on the fluorescence properties of molecularly imprinted microspheres
[0072] The Fe3O4@SiO2@AuNCs-MIPs polymer powder prepared in Example 3 was weighed, added to deionized water to prepare a 500 mg / L fluorescent imprinting polymer standard solution, and stored at 4°C in the dark for later use.
[0073] 1) Stability test
[0074] Take an appropriate amount of the above fluorescent imprinted polymer standard solution, shake it evenly at 25°C, measure the fluorescence value of the solution once at zero minute, and then test and record the fluorescence intensity with a fluorescence spectrophotometer every two minutes (within 1 hour). Each sample is measured in parallel 3 times and the average value is taken.
[0075] Figure 5The fluorescence intensity of Fe3O4@SiO2@AuNCs-MIPs changes with time. Under room temperature, the fluorescence was detected quickly after shaking evenly for 2 minutes within 60 minutes. The fluorescence of Fe3O4@SiO2@AuNCs-MIPs remained relatively stable. Therefore, it shows that the prepared MIPs have excellent fluorescence stability.
[0076] 2) Study on quenching response time
[0077] Take an appropriate amount of the above fluorescent imprinted polymer standard solution, add 10 ml of 20 mg / L sulfadiazine standard solution and shake evenly, measure the fluorescence value of the solution once at zero minute, and then test and record the fluorescence intensity with a fluorescence spectrophotometer every two minutes (30 min, each sample is measured in parallel 3 times, and the average value is taken.
[0078] Figure 6 This is a graph showing the fluorescence quenching response of Fe3O4@SiO2@AuNCs-MIPs to sulfadiazine over time. When 10 ml of 20 mg / L sulfadiazine is added, Fe3O4@SiO2@AuNCs-MIPs specifically binds to the template molecules through specific imprinted cavities and quenches in a relatively short time. The fluorescence intensity of the solution gradually weakens and reaches equilibrium after about 16 minutes. Therefore, the optimal response time of the fluorescent imprinted polymer to sulfadiazine is 16 minutes.
[0079] 3) Effect of different pH values on fluorescence quenching of Fe3O4@SiO2@AuNCs-MIPs
[0080] The pH value of the solution system was adjusted using a phosphate buffer solution (PBS buffer solution), and the fluorescence quenching experiment was performed within the pH range of 3-12.
[0081] Use acetonitrile / water (v / v=1:1) as solvent to prepare 100 mg / L sulfadiazine standard solution, and store it at 4°C in the dark.
[0082] Take 1.5 ml of multiple portions of the above fluorescent imprinted polymer standard solution in sequence and place them in multiple centrifuge tubes respectively, add 5 mL of sulfadiazine standard preparation solution to the multiple centrifuge tubes in sequence, and then make up each volume to 10 mL with PBS buffer solutions of different pH values to obtain multiple solutions with pH values of 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12 in sequence; shake and vibrate at room temperature and let stand for 16 minutes, then measure the fluorescence with a fluorescence spectrophotometer, measure each sample in parallel 3 times, and take the average value.
[0083] Figure 7The figure shows the change of the fluorescence quenching effect of sulfadiazine on Fe3O4@SiO2@AuNCs-MIPs at different pH values. When pH is less than 6, the fluorescence quenching effect of Fe3O4@SiO2@AuNCs-MIPs increases rapidly with the increase of pH. In the pH range of 6.0-8.0, the fluorescence quenching effect of Fe3O4@SiO2@AuNCs-MIPs increases slowly with the increase of pH, and reaches a peak value at pH = 8.0. When the pH is between 6.0 and 9.0, its fluorescence quenching performance remains relatively stable. When pH is greater than 9, the fluorescence quenching effect gradually weakens, but it is still higher than that in an acidic environment. Under strong acid and alkali conditions, the antibiotic will be destroyed, and strong acid and alkali will affect the fluorescence signal. Therefore, pH 8.0 is the optimal pH.
[0084] 4) Effect of different concentrations of template molecules on the fluorescence intensity of Fe3O4@SiO2@AuNCs-MIPs
[0085] Use acetonitrile / water (v / v=1:1) as solvent to prepare 200 mg / L sulfadiazine standard preparation solution, dilute it into sulfadiazine standard solutions of different concentrations (0-25 mg / L), and store it at 4°C in the dark.
[0086] Take 1.5 mL of fluorescent imprinted polymer standard solution and add it to 6 groups of centrifuge tubes respectively, dilute it with an equal amount of PBS buffer solution with pH = 8.0, mix it evenly, and prepare sulfadiazine standard solutions with concentrations of 0, 5, 10, 15, 20, and 25 mg / L respectively, and add them to centrifuge tubes; take 5 mL of sulfadiazine standard solutions with different concentrations respectively, shake them at room temperature for 16 minutes, and test and record the fluorescence emission spectrum of each sulfadiazine standard solution.
[0087] The Fe3O4@SiO2@AuNCs-NIPs prepared in the comparative example were subjected to the same experimental procedures as those for Fe3O4@SiO2@AuNCs-MIPs to compare the effects of different concentrations of template molecules on the fluorescence intensity of Fe3O4@SiO2@AuNCs-NIPs. Figure 8 This is the effect of different concentrations of template molecules on the fluorescence intensity of Fe3O4@SiO2@AuNCs-MIPs; Figure 8 In (a), after adding different concentrations of sulfadiazine SD (0-25 mg / L), the fluorescence intensity decreases with the increase of concentration, which is consistent with Figure 8The comparison in (b) shows that the decrease in fluorescence intensity of Fe3O4@SiO2@AuNCs-MIPs is greater than that of Fe3O4@SiO2@AuNCs-NIPs. This is because there are specific recognition holes in Fe3O4@SiO2@AuNCs-MIPs that correspond to the template molecule sulfadiazine in space and size, which can be adsorbed through hydrogen bonds. Therefore, the adsorption of sulfadiazine SD by Fe3O4@SiO2@AuNCs-MIPs is greater than the non-specific adsorption of sulfadiazine SD by Fe3O4@SiO2@AuNCs-NIPs.
[0088] 5) Fe3O4@SiO2@AuNCs-MIPs selection competition experiment
[0089] The selective competition experiment selected three sulfonamide antibiotics as structural analogs for comparison. The three structural analogs are: sulfathiazole, sulfadimethoxine, and sulfapyridine. Weigh 10 mg of the above sulfathiazole, sulfadimethoxine, and sulfapyridine respectively, use acetonitrile / water (v:v=1:1) as solvent to prepare a 200 mg / L standard mother solution, take a certain amount of the mother solution and dilute it to prepare a 20 mg / L concentration standard solution, and seal it in the refrigerator for later use.
[0090] Then, 1.5 mL of Fe3O4@SiO2@AuNCs-MIPs (500 mg / L) standard solution was added to a centrifuge tube, diluted with an equal amount of PBS buffer solution with pH = 8.0, and then mixed thoroughly. A series of prepared sulfonamide antibiotic standard solutions of the same concentration were added to the centrifuge tube in equal amounts, shaken at room temperature for 16 minutes, and the fluorescence emission spectra of the mixed solutions were recorded respectively. The Fe3O4@SiO2@AuNCs-NIPs prepared in the comparative example was carried out according to the same experimental steps as a control.
[0091] Fig. 9 The fluorescence quenching of Fe3O4@SiO2@AuNCs-MIPs and Fe3O4@SiO2@AuNCs-MIPs by four sulfonamide antibiotics is shown in the figure. As can be seen from the figure, sulfadiazine SD has the greatest quenching effect on Fe3O4@SiO2@AuNCs-MIPs. Although sulfathiazole and sulfapyridine are similar to sulfadiazine in structure, they are different in matching hole structures, so the fluorescence quenching effect is low. Sulfadimethoxine has the greatest structural difference from sulfadiazine, so its fluorescence quenching effect is the smallest. Since Fe3O4@SiO2@AuNCs-NIPs does not form a corresponding hole structure and cannot bind specifically, the fluorescence quenching effect of the other three sulfonamide antibiotics on Fe3O4@SiO2@AuNCs-NIPs is not much different.
[0092] 6) Real water sample analysis
[0093] The artificial lake water of Anhui University was taken as the actual sample and pretreated. The water sample was left to stand overnight, the supernatant was taken and filtered with a disposable filter head (0.22um) to obtain the sample solution; 20mg / L concentration of sulfadiazine standard solution was added to the sample solution respectively until the concentration of sulfadiazine was 1mg / L, 5mg / L, and 10mg / L, respectively, and stored in a refrigerator.
[0094] Table 1 Recovery rate of Fe3O4@SiO2@AuNCs-MIPs in actual samples
[0095] Watersample Added(mg / L) Found(mg / L) Recovery RSD (N=3,%) 1 1 1.0401 104.0 4.2 2 5 5.117 102.3 3.7 3 10 9.891 98.9 5.9
[0096] It can be seen from the data in Table 1 that a good recovery rate was obtained within the linear fitting range. The recovery rate was between 98.9% and 104.0%, and the relative standard deviation was less than 5.9%. The magnetic molecular imprinting fluorescence sensing system showed excellent performance in the determination of actual samples, and the fluorescence detection of the template molecule sulfadiazine SD was accurate and effective. Therefore, it can be used to detect sulfadiazine SD in a real environment.
[0097] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a magnetic fluorescent gold nanocluster molecularly imprinted polymer, characterized in that: The steps include: S1, Fe3O4 nanoparticles were coated with silica using a sol-gel method to obtain Fe3O4 nanoparticles coated with silica shell, which were recorded as Fe3O4@SiO2; S2, dispersing Fe3O4@SiO2 in anhydrous ethanol, and then adding 3-aminopropyltriethoxysilane for surface modification to obtain amino-functionalized Fe3O4@SiO2, recorded as Fe3O4@SiO2-NH2; S3, using the surface modification method, Fe3O4@SiO2-NH2 was combined with gold nanoclusters to obtain Fe3O4@SiO2@AuNCs; S4. Using molecular imprinting technology, sulfadiazine was used as the template molecule and a mixed silane coupling agent was used as the functional monomer to coat the molecular imprinting layer on the surface of Fe3O4@SiO2@AuNCs to prepare magnetic fluorescent gold nanocluster imprinted polymer Fe3O4@SiO2@AuNCs-MIPs.
2. The method for preparing the magnetic fluorescent gold nanocluster molecularly imprinted polymer according to claim 1, characterized in that: The preparation method of Fe3O4@SiO2 in step S1 is as follows: adding Fe3O4 nanoparticles to a 0.1-0.3M HCl aqueous solution in an amount of 0.01-0.03g / ml, separating and washing after ultrasonic dispersion for 20-50 minutes to obtain surface-modified Fe3O4 nanoparticles; mixing anhydrous ethanol, distilled water, ammonia water and tetraethyl orthosilicate in a volume ratio of 32:8:1:1 to obtain a mixed solution; adding 200-220ml of the mixed solution to 400-600mg of the surface-modified Fe3O4 nanoparticles and stirring overnight, separating the product, washing with distilled water, and vacuum drying to constant weight. The obtained black powder is Fe3O4 nanoparticles coated with a silica shell, recorded as Fe3O4@SiO2.
3. The method for preparing the magnetic fluorescent gold nanocluster molecularly imprinted polymer according to claim 1, characterized in that: The specific preparation method of Fe3O4@SiO2-NH2 in step S2 is as follows: disperse Fe3O4@SiO2 in anhydrous ethanol with a dispersion concentration of 0.01-0.03 g / ml, then add 3-aminopropyltriethoxysilane in anhydrous ethanol with an addition amount of 0.05-0.1 g / ml, and the mass ratio of Fe3O4@SiO2 to 3-aminopropyltriethoxysilane is 1:(4.5-5). After stirring and reacting for 10-15 hours under a protective atmosphere, the mixture is separated, washed with ethanol, and dried to obtain amino-functionalized Fe3O4@SiO2, which is recorded as Fe3O4@SiO2-NH2.
4. The method for preparing the magnetic fluorescent gold nanocluster molecularly imprinted polymer according to claim 1, characterized in that: The specific preparation method of Fe3O4@SiO2@AuNCs in step S3 is as follows: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is dissolved in morpholineethanesulfonic acid with a concentration of 0.1 mM and a pH of 7.0, and the dissolved concentration is 0.5-2 mg / ml to obtain a hydrochloride solution; N-hydroxysuccinimide is dissolved in distilled water, and the dissolved concentration is 0.5-2 mg / ml to obtain an N-hydroxysuccinimide solution; 90 mL of ultrapure water and 4 mL of 40-60 mM tetrahydrate of chloroauric acid are mixed and stirred evenly to obtain solution 1; 80-100 mg of L-reduced glutathione GSH is dissolved in 4 mL of ultrapure water to obtain solution 2; Solution 2 is added to Solution 1, heated to 60-80° C. and stirred vigorously, and after the solution turns slightly yellow, 1 mL of 28-32% (w / v) threonine Thr aqueous solution is added, and the mixture is reacted. The product should be dialyzed overnight using a dialysis bag for 20-25 hours to obtain a solution containing carboxyl-functionalized gold nanoclusters AuNCs; the hydrochloride solution and the solution containing carboxyl-functionalized gold nanoclusters AuNCs are mixed, and then N-hydroxysuccinimide solution is added, the volume ratio of the three is 6:10:6, and the mixture is stirred; 50-70 mg of Fe3O4@SiO2-NH2 and 0.05-0.2 mM morpholineethanesulfonic acid with a pH of 5-8 are added to the mixture, and the volume ratio of the added volume of morpholineethanesulfonic acid to the solution containing carboxyl-functionalized gold nanoclusters AuNCs is 5:1, after ultrasonic dispersion, stirring overnight in the dark, separation, and washing with a phosphate buffer solution with a pH of 7.0 and a concentration of 0.01 M to obtain Fe3O4@SiO2@AuNCs.
5. The method for preparing the magnetic fluorescent gold nanocluster molecularly imprinted polymer according to claim 1, characterized in that: The preparation method of Fe3O4@SiO2@AuNCs-MIPs in step S4 is as follows: 80-150 mg of Fe3O4@SiO2@AuNCs nanoparticles are added to 30-50 ml of phosphate buffer solution and mixed evenly. The concentration of the phosphate buffer solution is 10 mmol L -1 , pH 7.0, then add 0.15-0.2mmol mixed silane coupling agent, add 10mg sulfadiazine as template molecule, stir evenly, add 60-100μl tetraethyl orthosilicate and 60-100μl ammonia water, the molar ratio of template molecule to mixed silane coupling agent is 1:4, stir continuously for 12-20h at room temperature, after the reaction is completed, separate the solid product by centrifugation, then wash repeatedly with a mixed solvent of methanol and acetic acid in a volume ratio of 9:1, until the supernatant can no longer detect the template molecule sulfadiazine by ultraviolet spectrophotometer, and then vacuum dry, so as to obtain magnetic fluorescent gold nanocluster imprinted polymer, recorded as Fe3O4@SiO2@AuNCs-MIPs.
6. The method for preparing the magnetic fluorescent gold nanocluster molecularly imprinted polymer according to claim 2, characterized in that: In step S1, the black powder Fe3O4@SiO2 is dried in a vacuum drying oven at a temperature of 40-60°C, and the separated product is washed with distilled water and anhydrous ethanol in sequence; the reaction products are separated in steps S1 and S2 by adsorption separation using a strong magnet.
7. The method for preparing the magnetic fluorescent gold nanocluster molecularly imprinted polymer according to claim 1, characterized in that: The mixed silane coupling agent described in step S4 is APTES.
8. A magnetic fluorescent gold nanocluster molecular imprinting polymer obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the magnetic fluorescent gold nanocluster molecular imprinting polymer according to claim 8 in fluorescence detection of sulfonamide antibiotics.
10. The use of the magnetic fluorescent gold nanocluster molecular imprinted polymer in fluorescence detection of sulfonamide antibiotics according to claim 9, characterized in that: The aqueous solution of the magnetic fluorescent gold nanocluster molecular imprinting polymer was mixed with sulfadiazine, and the changes in fluorescence intensity before and after the mixing were compared.
Citation Information
Cited By
Magnetic fluorescent gold nanocluster molecularly imprinted polymer, preparation method therefor, and use thereof
WO2026077476A1